2020
DOI: 10.1101/2020.07.11.20151365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased serum levels of inflammaging marker miR-146a are associated with clinical response to tocilizumab in COVID-19 patients

Abstract: Background. Current COVID-19 pandemic poses an unprecedented threat to global health and healthcare systems. At least in western countries, the most amount of the death toll is accounted by old people affected by age-related diseases. In this regard, we proposed that COVID-19 severity may be tightly related to inflammaging, i.e. the age-related onset of inflammation, which is responsible for age-related diseases. It has been reported that systemic hyper-inflammation may turn to be detrimental in COVID-19 patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…In addition, no relevant studies were identi ed by searching the reference lists of the selected studies. After careful full-text reading, only seven studies [22][23][24][25][26][27][28] met the inclusion criteria and thus were included in the review. A owchart of the literature search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, no relevant studies were identi ed by searching the reference lists of the selected studies. After careful full-text reading, only seven studies [22][23][24][25][26][27][28] met the inclusion criteria and thus were included in the review. A owchart of the literature search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the seven studies included in this scoping review are summarized in Table 1. All seven studies were published in English, reported between October 2020 and January 2021, and published as research articles [22][23][24][25][26][27][28]. Four of them were conducted in China [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs have been revealed to play crucial roles in a complex network of interaction that don't respond to the tocilizumab treatment, the levels of miR-146a-5p were decreased in their serum. MiRNAs in the blood, such as miR-146a-5p, -21-5p, and -126-3p can be potential biomarkers to provide a molecular link between inflammation and the COVID-19 [20]. In an experimental study on rat and human derived cardiomyocytes, it has been shown that both ACE2 mRNA and protein levels are inhibited by miR-200c, which can also be the potential target of the miRNA therapeutics in cardiomyocyte-affected infections [21].…”
Section: Sars-cov-2 Replication and Pathogenesismentioning
confidence: 99%